Analisis Strategi Likuidasi Maskapai Penerbangan PT. Metro Batavia - Gusmanto Gusmanto; Saladin Ghalib; Noor Hidayati (JURNAL BISNIS DAN PEMBANGUNAN, 2016)
This research aimed to find out the fundamental things that made the company management hadto exterminate PT.Metro Batavia, and to do some assessments from business aspect of PT.Metro Bataviamanagement, whetherthe decision to exterminate the company has already precise.This research was executed at Curator officeof PT.Metro Batavia in Jakarta. The research utilized qualitative approach method that emphasizedon secondary data.Due to factors identification of IFAS and EFAS at PT.Metro Batavia, the result of the research showed that liquidation strategy was the best decision to make, it was proven by result of IFAS calculation at -0,17 (weak) and EFAS at -0,32 (low) shown by Table 5.15: MATRIX INTERNAL-EXSTERNAL (IE MATRIX), and the management decision to liquidating PT. Metro Batavia has beenaccurate, since it confirmedby strategic management analysis and its execution did not against the business ethics.  Keywords: Liquidation, PT.Metro Batavia